Analisis Kekuatan dan Potensi Resonansi pada Pondasi Diesel Generator Menggunakan Metode Elemen Hingga - Qoniah Ardelia; Agung Prasetyo Utomo; Priyambodo Nur Ardi Nugroho (Infotekmesin, 2025)
The ship’s electrical system heavily relies on a safe and reliable diesel generator foundation. However, many foundation designs currently used in the industry have not been comprehensively validated against classification standards, nor analyzed for resonance potential and fatigue life. This study aims to develop a diesel generator foundation design that complies with ship structural safety standards based on Lloyd’s Register (LR) regulations. The methods used include 3D modeling, structural and resonance analysis using the Finite Element Method (FEM), and validation through manual calculations. The results show that the initial design does not meet safety standards, while the LR-based design yields a maximum stress of 164.01 MPa and a maximum deformation of 0.99981 mm, with a fatigue life reaching 28 years. Both designs indicate no potential for resonance. This study recommends the LR-based foundation design as the optimal solution to ensure structural integrity, long service life, and compliance with maritime safety regulations.